Analisa Performansi Photovoltaic 200 WP dan Pompa Air Dc pada Implementasi Sistem Pembangkit Listrik Tenaga Surya (PLTS) - Marshal Jawahar Al Nehru; Bengawan Alfaresi; Feby Ardianto (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Water is one of the most widely used natural products by humans, such as for daily needs for drinking, cooking, bathing, washing and others, even industry, agriculture, offices all need water. Water is a basic human need, but it is still found in some areas with limited and difficult to reach water sources. This study aims to analyze the performance of photovoltaic (solar panels) and the results of the electric pump in the implementation of a solar power generation system (PLTS). In this study, designing a solar power plant (PLTS) that is connected to a solar charge controller and connected directly to a water pump system using a battery as a source. Based on the results of the study, it shows that the higher the solar radiation, the higher the output power of the 200 Wp PV module. Likewise, changes in reservoir height greatly affect changes in water discharge and currents. The higher the reservoir well distance, the smaller the water discharge and the higher the reservoir well distance also affects the increase in current.